2016
DOI: 10.4049/jimmunol.1502490
|View full text |Cite
|
Sign up to set email alerts
|

Highly Dynamic Transcriptional Signature of Distinct Macrophage Subsets during Sterile Inflammation, Resolution, and Tissue Repair

Abstract: Macrophage gene expression determines phagocyte responses and effector functions. Macrophage plasticity has been mainly addressed in in vitro models that do not account for the environmental complexity observed in vivo. In this study, we show that microarray gene expression profiling revealed a highly dynamic landscape of transcriptomic changes of Ly6CposCX3CR1lo and Ly6CnegCX3CR1hi macrophage populations during skeletal muscle regeneration after a sterile damage. Systematic gene expression analysis revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
212
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(235 citation statements)
references
References 50 publications
(76 reference statements)
15
212
0
1
Order By: Relevance
“…Although alternatively activated macrophages have been implicated in tissue repair and PPARγ has been reported to be a regulator of alternative macrophage polarization (Odegaard et al, 2007), we have previously reported that muscle Ly6C + and Ly6C − macrophages do not correspond to canonical alternatively polarized macrophage populations (Varga et al, 2016) in the CTX model. Therefore it is not surprising that, in this model PPARγ is controlling genes other than alternative macrophage related ones, reported to be PPARγ–dependent in other tissue compartments and contexts (Odegaard et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…Although alternatively activated macrophages have been implicated in tissue repair and PPARγ has been reported to be a regulator of alternative macrophage polarization (Odegaard et al, 2007), we have previously reported that muscle Ly6C + and Ly6C − macrophages do not correspond to canonical alternatively polarized macrophage populations (Varga et al, 2016) in the CTX model. Therefore it is not surprising that, in this model PPARγ is controlling genes other than alternative macrophage related ones, reported to be PPARγ–dependent in other tissue compartments and contexts (Odegaard et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…This, coupled with the macrophage continuum, has led to inconsistencies with regard to identification and nomenclature across fields and across species (Murray et al , 2014). Skeletal muscle macrophages have primarily been studied in rodent models of injury, where the M1 versus M2 macrophage classification has proven useful (Smith et al , 2008; Chazaud et al , 2009; Tidball and Villalta, 2010, Kharraz et al , 2013; Novak and Koh, 2013; Saclier et al , 2013b; Rigamonti et al , 2014; Tidball et al , 2014; Wang et al , 2014; Sciorati et al , 2016; Varga et al , 2016; Mackey and Kjaer, 2017). The skeletal muscle response to injury is characterized by highly orchestrated temporal processes.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages designated as classical inflammatory “M1” macrophages predominate early after injury, while alternatively-activated “M2” macrophages (AAMs) orchestrate the later phases of tissue repair. Inflammatory macrophages respond to tissue damage signals and upregulate genes associated with alarmins and acute inflammatory-phase proteins [10]. Later during the inflammatory response, AAMs are a potent source of insulin-like growth factor (IGF-1) required for muscle regeneration [11] and highly express genes encoding extracellular matrix (ECM) and ECM remodeling proteins [10].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory macrophages respond to tissue damage signals and upregulate genes associated with alarmins and acute inflammatory-phase proteins [10]. Later during the inflammatory response, AAMs are a potent source of insulin-like growth factor (IGF-1) required for muscle regeneration [11] and highly express genes encoding extracellular matrix (ECM) and ECM remodeling proteins [10]. Though some resting tissues such as the lung, liver, and brain have macrophage populations that are seeded embryonically [12, 13], skeletal muscle possesses very few macrophages during homeostasis [3].…”
Section: Introductionmentioning
confidence: 99%